Niger : Third Review Under the Extended Credit Facility Arrangement, Request for Waiver of Nonobservance of Performance Criterion, and Request for Augmentation of Access-Press Release; Staff Statement; and Statement by the Executive Director for Niger. (IMF Staff Country Reports; Country Report ;, 2018)
Niger faces daunting development challenges, aggravated by terrorist incursions, low uranium export prices, and climate change. Nonetheless, GDP grew by a respectable 5 percent in the past two years. It should average 7 percent over the next five years thanks to reforms, substantial donor support, several large-scale projects, and a one-time boost from the projected commencement of crude oil exports in 2022.